The violence volcano : reducing the threat of workplace violence - Van Fleet, David D.; Van Fleet, Ella W. (Emerald Publishing Limited : IAP, Information Age Publishing, 2010)
The Violence Volcano is for managers and workers in all types of business and government organizations, including law enforcement and other first-responders. Its purpose is to assist all organizations and their employees in fulfilling their obligations under U.S. Government regulations to reduce the risks of any and all forms of violence that affect workers during the time they are carrying out their duties as employees. The Violence Volcano is written at an appropriate level for either self-study, training programs, or classroom settings. It could be used as a supplement in business, educational administration, criminal justice and law enforcement classes, or other academic and trade programs. Key features of the book: * Uses the volcano metaphor to provide a simple and unique way to help readers under stand and remember how violence builds. * Provides a broader approach than other books toward recognizing and dealing with the issue of workplace violence, including both internal and external causes as well as signs of impending acts of violence. * Identifies and discusses the nature and complexity of violence in a variety of workplaces. * Helps management compare violence prevention costs with the immediate and direct costs plus the delayed and hidden costs of violent incidents at work. * Helps management, employees, and law enforcement personnel recognize environmental and organizational influences on employee behavior. * Helps management and employees develop an awareness of personal characteristics and work behaviors that build toward violent behavior, so that timely intervention can perhaps eliminate the threat of violence. * Assists management in establishing a crisis management team, an organizational crisis plan, a violence intervention plan, and a post-violence trauma plan. * Develops a comprehensive definition of workplace violence and examines its rapid growth. * Suggests administrative ways of reducing risks, such as establishing anti-violence policies, improving asset security, and providing an adequate support system. * Introduces the topics of legal responsibilities and liabilities, and working with law enforcement.